A test of the predictive validity of hypothetical intentions to offend - Exum, Myron Lyn (Journal of crime and justice, 2018)
Researchers commonly use hypothetical intentions to offend as proxies for real-world offending behavior. The current study examined the predictive validity of these hypothetical intentions, as well as the consequences of using offending intentions in statistical models of decision-making. Undergraduate students were asked to self-report their intentions to cheat on a hypothetical online exam for which they were unprepared. Minutes later, they completed a difficult online trivia test for course credit. Students who performed well on the trivia test were presumed to have cheated. Hypothetical intentions to cheat were found to predict actual cheating at a rate no better than chance. Furthermore, while several factors were found to be predictive of hypothetical cheating, none were predictive of actual cheating. This incongruence between intentions and behavior may be attributed to the different emotional reactions evoked by hypothetical and real-world offending opportunities. Implications for research on offender decision-making are discussed.